MULTIENZYME PRODUCING HALOALKALIPHILIC BACTERIA FROM LONAR LAKE - TAMBEKAR DH; DHUNDALE VR (International Journal of Pharma and Bio Sciences, 2013)
Lonar Lake is interesting ecosystem system for studies on microbial diversity and its function in extreme environment. The Lonar Lake is saline alkaline lake having salinity 7000 mg/L and pH 10.5 and harbors various unidentified, unique haloalkaliphilic bacterial species which produces alkaliphilic enzymes. The present study deals with the isolation and characterization of multienzyme producing bacteria from Lonar Lake. Aerobic, haloalkaliphilic bacteria were isolated and characterized from sediment and water from Lonar Lake. The fifty five cultures were isolated using different enrichment media. Out of them eight bacterial strains were screened for 16S rRNA sequencing on the basis of their amylolytic, proteolytic and lipolytic activity. The phylogenetic position indicated the Lonar lake bacterial strains were related to phylum Firmicutes and belongs to genera Bacillus and are Bacillus flexus (1), Bacillus pseudofirmus (4), Bacillus cereus (1), Bacillus sp AW4(3) and Bacillus sp OBW3(2). The Bacillus cereus was found prominent amylase and protease producer while Bacillus flexus was found an efficient lipase producer. All these bacterial strains showed optimum activity at pH 10 and 45°C and found to be biotechnologically important enzyme producer which have prominently useful in pharmaceutical, leather, detergent and textile industry.